Protocol for the REVISIT-BPD Trial, a Randomized Controlled Trial Testing the Effectiveness of an Internet-Based Self-Management Intervention in the Treatment of Borderline Personality Disorder (BPD) - Klein, Jan Philipp; Hauer, Andrea; Berger, Thomas; Fassbinder, Eva; Schweiger, Ulrich; Jacob, Gitta (Frontiers in Psychiatry, 2018)
Introduction: Borderline Personality Disorder (BPD) is a prevalent condition that is often under-treated. This is partly because very few psychotherapists offer treatment for this disabling disorder. Internet-based self-management interventions could contribute to reducing the treatment gap but – mainly due to safety concerns – these have never been tested for BPD in controlled trials. Methods: Patients with BPD will be recruited primarily via the internet and randomized to two groups: care as usual (CAU) alone ) or the self-management intervention priovi® in addition to CAU . At the end of the diagnostic interview, all participants will discuss an emergency plan. The main outcome measure is the clinician-rated symptom severity using the BPD Severity Index (BPDSI). Secondary outcome measures include a range of self-reported scales, an SCID-diagnosis of BPD and several safety parameters including serious adverse events (e.g., a life-threatening event, hospitalization or suicide attempt). Discussion: This trial will evaluate the effectiveness of the self-management intervention, priovi, in reducing symptoms of BPD. It will also assess the safety of its use in this target population. If successful, this intervention would be the first comprehensive internet intervention for the treatment of BPD and complement the wide range of internet interventions effective in treating other mental disorders, particularly depression and anxiety disorders. Trial Registration: NCT03418142 (clinicaltrials.gov) on January 23rd 2018. Trial status: recruiting, currently N = 108 (July 2018)